Production of transgenic rice (indica cv. MR219) overexpressing Abp57 Gene through Agrobacterium-mediated transformation - Tan, Lay-Wen; Zuraida A. Rahman,; Goh, Hoe-Han; Hwang, Duk-Ju; Ismanizan Ismail,; Zamri Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Agrobacterium-mediated transformation of indica rice is undoubtedly a challenging task due to the rice recalcitrant nature to transformation process. Therefore, optimization of the transformation protocol is important for specific indica rice cultivar to ensure effectiveness of the transformation. In this study, crucial parameters affecting Agrobacterium-mediated transformation were optimized to obtain transgenic rice of local rice cultivar (indica MR219). Embryogenic calli were chosen for inoculation with Agrobacterium tumefaciens strain LBA4404 harbouring a binary vector pH2GW7-ABP57 containing gene of interest, Auxin binding protein 57 (Abp57). The parameters that have been optimized were the immersion time, co-cultivation period, acetosyringone concentration and co-cultivation temperature. A total of four days co-cultivation period and 30 min immersion of embryogenic callus are optimum for the transformation of MR219 with transformation efficiency of 26.4% and 16.0%, respectively. Acetosyringone at 200 μM and co-cultivation at 28°C also gave the highest transformation efficiency (14.4 and 18.4%, respectively). Meanwhile, inclusion of 20 g/L maltose+20 g/L sorbitol into the regeneration media has significantly improve the transformed somatic embryos growth and increase the regeneration efficiency up to 40.0%. The results of polymerase chain reaction (PCR) and reverse transcription-polymerase chain reaction (RT-PCR) indicated that the transgene was successfully integrated and overexpressed in transgenic rice of MR219. In conclusion, significant improvement in transformation efficiency for rice cv. MR219 has been obtained by using the optimised protocol for transformation and regeneration developed in this study.